2012
DOI: 10.1177/0192623312464308
|View full text |Cite
|
Sign up to set email alerts
|

Anchoring Hepatic Gene Expression with Development of Fibrosis and Neoplasia in a Toxicant-induced Fish Model of Liver Injury

Abstract: Fish have been used as laboratory models to study hepatic development and carcinogenesis but not for pathogenesis of hepatic fibrosis. In this study, a dimethylnitrosamine-induced fish model of hepatic injury was developed in Japanese medaka (Oryzias latipes) and gene expression was anchored with the development of hepatic fibrosis and neoplasia. Exposed livers exhibited mild hepatocellular degenerative changes 2 weeks post-exposure. Within six weeks hepatic fibrosis/cirrhosis was evident with development of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 69 publications
1
8
0
Order By: Relevance
“…Tgfb1 encodes a multifunctional peptide which regulates proliferation, differentiation, adhesion, migration, and many other physiological and pathological functions (Causey et al, 2012;Massague and Gomis, 2006). In the liver, Tgfb1 encodes a master regulator of ECM production and hepatic stellate cell activation after toxic chemical injury (Ghosh and Vaughan, 2012;Liu, 2008;Van Wettere et al, 2013). In contrast, the inducible form of TGF-b (Tgfbi) was downregulated in the livers with microscopic evidence of fibrosis in this study (Figure 11; Supplementary Table 1).…”
Section: Gene Signatures In Hepatotoxic Injurymentioning
confidence: 64%
“…Tgfb1 encodes a multifunctional peptide which regulates proliferation, differentiation, adhesion, migration, and many other physiological and pathological functions (Causey et al, 2012;Massague and Gomis, 2006). In the liver, Tgfb1 encodes a master regulator of ECM production and hepatic stellate cell activation after toxic chemical injury (Ghosh and Vaughan, 2012;Liu, 2008;Van Wettere et al, 2013). In contrast, the inducible form of TGF-b (Tgfbi) was downregulated in the livers with microscopic evidence of fibrosis in this study (Figure 11; Supplementary Table 1).…”
Section: Gene Signatures In Hepatotoxic Injurymentioning
confidence: 64%
“…All medaka embryos used were at stage 21 because our previous study had revealed that this stage was more sensitive than other stages to SNC (Kashiwada et al, 2012). Japanese medaka is commonly used as a typical freshwater fish model in toxicology (Van Wettere et al, 2013) and ecotoxicology (Kashiwada et al, 2008). Although Japanese medaka is a freshwater fish, it can live in not only freshwater but also brackish water or seawater.…”
Section: Medaka Eggsmentioning
confidence: 99%
“…The changes in the liver of DMN-exposed fish were similar to those described by Hobbie et al ., (2011) and Van Wettere et al . (2012).…”
Section: Resultsmentioning
confidence: 96%
“…However, in this study, exposure to DMN was used to induce oval cell hyperplasia (Thoolen et al ., 2010; Hobbie et al ., 2011; Van Wettere et al ., 2012). The subset of DMN-exposed livers that exhibited prominent oval cell hyperplasia was selected and evaluated by IHC and TEM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation